The value of D-dimer in the prognosis of dilated cardiomyopathy: a retrospective cohort study - Huang, Yuan; Yang, Li-Hua; Li, Yu-Xin; Chen, Hong; Li, Jia-Hao; Su, Hua-Bin; Gui, Chun; Su, Qiang (Scientific reports, 2024)
D-dimer is a biomarker of coagulation and fibrinolytic system activation in response to the hypercoagulable state of the body. The research aimed to analyze the value of D-dimer in the prognosis of patients with dilated cardiomyopathy (DCM). Patients admitted to our center for the first time with DCM were enrolled consecutively. The clinical characteristics variables were obtained from the electronic medical record system, and the prognostic information was obtained using telephone return visits and a review of repeated hospitalization records. Univariate and multivariate Cox regression was used to explore the association of D-dimer with all-cause mortality. Smooth curve fitting, threshold saturation effect analysis, and subgroup analysis were performed. Ultimately, 534 patients were included. After a follow-up of the enrolled patients, 485 patients obtained prognostic information, of which 159 died from all causes, and the main cause of death was heart failure (89/159), the sudden death accounted for about 17%. The independent positive association between D-dimer and all-cause mortality remained unchanged in both unadjusted and adjusted Cox regression models. In the fully adjusted model, each standard deviation increase in D-dimer was associated with a 14% increase in all-cause mortality (HR = 1.14; 95% CI: 1.02 ~ 1.27; P < 0.05). Curve fitting and threshold effect analysis showed an inflection point in the relationship between D-dimer and all-cause mortality (non-linear test: P = 0.03). When D-dimer was equal to 362ng/ml, HR = 1; and as the value increased, the risk of all-cause mortality increased by 34.7% for every 2-fold increase in D-dimer gradually (HR = 1.347; 95% CI: 1.069 ~ 1.697; P = 0.012). In subgroup analysis, D-dimer and BMI had a significant interaction on all-cause mortality, with a significantly increased risk of all-cause mortality in subjects with BMI ≥ 25 kg/m 2 (HR = 1.99; 95% CI: 1.34 ~ 2.97; P < 0.01). The ROC curve showed that D-dimer was a good predictor of all-cause mortality, and the areas under the curve at 1-, 3-, and 5-year were 0.71, 0.64, and 0.59, respectively. In addition, D-dimer improved the predictive performance of the MAGGIC heart failure score in patients with DCM. D-dimer is not only independently associated with all-cause mortality in DCM patients, but also has good predictive value, suggesting that D-dimer may be an early and useful marker for improving the management of DCM patients.